Sociodrama on communication skills of students with introverted personality in senior high school - Sari, Yulia Novita; Astuti, Budi (COUNS-EDU: The International Journal of Counseling and Education)
The ability of students to communicate is a very important factor for achieving success in life. Many factors influence students' communication skills, can be factors from outside the individual or from within the individual. One of the factors within this individual is personality. Individuals are born with different personalities that greatly affect the way they communicate with their environment. The purpose of this study was to determine the communication skills of introverted personalities towards the use of group guidance services through sociodrama. The method used in this study is a single subject design. The results show that in the subject one mean level of baseline (A) is 78 mean level of intervention (B) is 125.3 while in subject two shows the mean level of baseline (A) is 80.67 and the mean level of intervention (B) is 129. So , the conclusion there is the influence of the use of sociodrama to improve the communication skills of Students with Introverted Personality In Senior High School.